Exogenous Application of Thidiazuron, Carbaryl, Ethephon, and Lime Sulphur Promotes Flower Abscission and Suppresses Tea Pests in the Tea Plant Camellia sinensis (L.) O. Kuntze - Meina Jin; Xiaoyue Lun; Ruirui Zhang; Yu Zhang; Xiangzhi Zhang; Feiyu Guan; Liping Wang; Yiheng Ying; Zhengqun Zhang; Xiuxiu Xu (Agriculture)
Tea plants Camellia sinensis (L.) O. Kuntze consume substantial quantities of water and nutrients during the flowering period, which can adversely affect the yield and quality of tea plants. Therefore, the effects of thidiazuron, carbaryl, ethephon, and lime sulphur on flower buds and flower abscission in tea plants were investigated. The photosynthetic characteristics and biochemical components, the electrical conductivity of leaves, and the occurrence of insect pests and frost damage in the tea plants were assessed following the exogenous application of these chemicals. The results showed that 0.015, 0.03, and 0.06% thidiazuron, 0.08% ethephon, and 2.0 and 3.0% lime sulphur significantly promoted tea flower buds and flower abscission. Thidiazuron notably increased the concentrations of total amino acids, caffeine, catechin, and soluble sugar in tea leaves while reducing leaf electrical conductivity to some extent. Additionally, it also suppressed the occurrence of Empoasca onukii Matsuda (Hemiptera: Cicadellidae) and Apolygus lucorum Meyer-Dür (Hemiptera: Miridae). Furthermore, thidiazuron enhanced both the length and weight of tea shoots the following early spring. Application of 3.0% lime sulphur enhanced chlorophyll a and b, carotenoid, catechin, and caffeine and decreased the number of Aleurocanthus spiniferus Quaintanca (Hemiptera: Aleyrodidae) on the tea plants. However, no significant differences in frost damage were observed across treatments. Overall, exogenous application of the chemicals, particularly thidiazuron, effectively reduced flower production, altered key biochemical components, controlled tea pests, and ultimately enhanced tea productivity.